Pengaruh Invesment Opportunity Set, Kinerja Keuangan dan Struktur Aset terhadap Nilai Perusahan pada Perusahaan Perhotelan, Resort Serta Cruise Line akan Terdaftar di BEI Tahun 2018-2022 - Putri Yulia Ningsih; Sandra Dewi (Transformasi: Journal of Economics and Business Management, 2024)
This research aims to determine, anaIyze and expIain the influence of the Investment 0pportunity Set, FinanciaI Performance, Asset Structure on company value, to optimize company value which can reflect the condition of a company through the company's share price. The sample in this research is 12 companies in hotel companies , resorts, cruise lines listed on the IDX 2018-2022. Data analysis in this research used purposive sampling. The method used is descriptive analysis with a quantitative approach and using descriptive methods with the help of SPSS version 24 to process it. Based on the research results, it can be seen that (1) Investment opportunity set has a positive and significant effect on company value as seen from the results of the t test research with sig 0, 00 ≤ 0.05 in hotel, resort, cruise line companies 2) financial performance does not have a positive effect on company value as seen from the results of the t test research with sig 0.510 ≥ 0.05 in hotel, resort, cruise line companies; (3) asset structure does not have a negative effect on company value as seen from the results of the t test research with sig 0.111 ≥ 0.05 in hotel, resort and cruise line companies; (4) Investment opportunity set, performance and asset structure on company value have a partial effect on company value in hotel, resort and cruise line companies listed on the Indonesia Stock Exchange 2018-2022.